2018
DOI: 10.1002/jcp.26872
|View full text |Cite
|
Sign up to set email alerts
|

Influence of all‐trans retinoic acid on sperm metabolism and oxidative stress: Its involvement in the physiopathology of varicocele‐associated male infertility

Abstract: The mechanisms by which varicocele affects fertility remain undetermined. Vitamin A (all-trans retinoic acid [ATRA]) is required for fertility and normal spermatogenesis; however, the mechanisms driving its action are not defined yet. Previously, we demonstrated in varicocele sperm a reduced RARα expression and that ATRA influence sperm performance. To further define vitamin A significance in male gamete and in the physiopathology of varicocele, we tested for the first time ATRA action on human sperm metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…Although the antioxidant ingredients, dosages, duration of treatment, and parameters measured differed significantly from one study to another, major improvements were observed including a favorable effect on spermatogenesis, sperm count, motility, morphology and integrity of sperm DNA, enzymatic and non‐enzymatic antioxidant status of testicular tissue, and gonadotropin and testosterone levels 24,25,31‐34 . Antioxidant supplementation has also been the subject of several studies in VCL patients 31,32,35‐37 . Here too, despite the great heterogeneity between clinical studies, beneficial effects were notable.…”
Section: Reactive Oxygen and Nitrogen Species (Ros/nos) And Vclmentioning
confidence: 99%
“…Although the antioxidant ingredients, dosages, duration of treatment, and parameters measured differed significantly from one study to another, major improvements were observed including a favorable effect on spermatogenesis, sperm count, motility, morphology and integrity of sperm DNA, enzymatic and non‐enzymatic antioxidant status of testicular tissue, and gonadotropin and testosterone levels 24,25,31‐34 . Antioxidant supplementation has also been the subject of several studies in VCL patients 31,32,35‐37 . Here too, despite the great heterogeneity between clinical studies, beneficial effects were notable.…”
Section: Reactive Oxygen and Nitrogen Species (Ros/nos) And Vclmentioning
confidence: 99%
“…The bone marrow lipid composition does not strictly depend only on lipids dietary intakes and may act in bone homeostasis as a key regulator. Palmitic and stearic saturated fatty acids may result in being lipotoxic to bone [206,207] and impair the OBL physiology [208,209], whereas palmitoleic, oleic, and linoleic unsaturated fatty acids seem to promote OBL differentiation, survival, and mineralization activity [206,209,210], while inhibiting OCL both differentiation and function [211,212]. Considering the association with bone fragility [213,214], it has been suggested that bone marrow saturated index, the proportion of saturated fatty acids to total fatty acids, to be a potential biomarker for osteoporosis [215].…”
Section: Bone Marrow Lipids Composition and Bone Healthmentioning
confidence: 99%
“…It is important for cell growth, communication, immune function, and reproduction. It can be obtained from plant and animal resources, food products, and supplements [112]. The antioxidant activity of vitamin A is diverse: it is a chain-breaking antioxidant that reacts with peroxyl radicals before they fuel peroxidation in the lipid phase and, consequently, hydroperoxide formation [113].…”
Section: Vitamin Amentioning
confidence: 99%